PRIMITIVE CONSTITUTIONALISM AS A SUBSTRATUM FOR THE EMERGENCE OF THE IDEA OF MATERIAL CONSTITUTION - Lopes Queiroz, Joao Eduardo [UNESP] (Iustel, 2021)
This study is about the importance of the movements of regulation of the society that occurred in the old age for the formation of the ideary dominant constitutionalism in the contemporary period. It addresses the existence of a primitive constitutionalism, inaugurated by the Hebrews and strengthened by the Greeks and the Romans. It concludes, in the end, by the existence of material constitutions in those periods, and that it was tributary to the formation of modern constitutionalism and consequently to the contemporary models of existing formal constitutions.
Keywords: Constitutionalism; Primitive Constitutionalism; Material Constitution